Comparison of Effectiveness Between Ultrasound-Guided and Blind Corticosteroid Injections in Plantar Fasciitis: A Systematic Review and Meta-Analysis - Hoa Ngan Doan; Yoo Jin Choo; Min Cheol Chang (Life, 2025)
The effectiveness of ultrasound (US)-guided compared with blind corticosteroid injections for the treatment of plantar fasciitis (PF) remains uncertain. This meta-analysis aimed to evaluate the clinical benefits of US-guided over blind injections in patients with PF. A systematic search of PubMed, Embase, Web of Science, and Scopus was conducted, collecting articles published up to 20 April 2025. Randomized controlled trials comparing US-guided and blind corticosteroid injections for PF were included. The extracted outcome measures, i.e., visual analog scale (VAS), heel tenderness index (HTI), tenderness threshold (TT), and plantar fascia thickness, were assessed at short- (2–6 weeks) and long-term (≥12 weeks) follow-ups. Compared with the blind injection group, the US-guided group showed significantly greater improvement in TT at both short- and long-term follow-ups, as well as a greater reduction in plantar fascia thickness. However, no significant differences were found between the two groups in VAS and HTI scores. US-guided corticosteroid injections provide superior clinical benefits compared with blind injections in patients with PF, particularly in enhancing mechanical pain tolerance and reducing plantar fascia thickness. Nevertheless, these findings should be interpreted with caution due to the limited methodological quality of the included studies.